Assessing adaptation options for climate change: A guide for coastal communities in the Coral Triangle of the Pacific 4. Decision-tree and partial cost-benefit analyses - WorldFish (2013)
Introduction Assessing options for adapting to climate change is an important part of building resilient fishing and farming communities. This brochure is part of a series that collectively detail how a community-based assessment of climate change was used in partnership with coastal communities and provincial and national-level stakeholders in Timor-Leste and Solomon Islands. The assessment contains four distinct, but related, steps (Fig 1) focused on supporting community-level decision-making for adaptation through a series of participatory action research activities. Each brochure in this series details a specific activity in the four-step assessment. This series of eight brochures is primarily aimed for use where resources are limited or where it is more appropriate to use a rapid, qualitative and non-data intensive method of assessment. Community leaders, local NGOs and regional and national-level government representatives in developing countries may find this series useful. In this brochure we provide details of an activity relating to the ‘Evaluation of options’ step of the assessment, research conducted with farmers and fishers to assess the economic implications of adopting different adaptation actions. More specifically, the following questions were posed: • What are key decisions and design steps needed in developing specific fishing and farming-related adaptations to enable them to be implemented and managed over time? • What are the relative partial costs and benefits of the different adaptations?